Effect of Mixed Yeast Strains and Additives on the Quality of Long-Term Refrigerated Fermented Doughs - Jun Liu; Lei Yang; Yingji Wang; Mengnan Wang; Qilong Qian; Lei Lou; Zhe Wu; Jiamin Zhu; Xiaoyu Fu; Jun Xing; Yixian Tu; Yun-Guo Liu (Foods)
With a prolonged refrigeration time, dough becomes syruped and the gluten strength is weakened, which negatively affects the texture of the dough. At the same time, differences in the growth and metabolism of different yeasts lead to large differences in the physicochemical properties of the dough and the final quality of the product. Therefore, in this study, suitable additives and non-Saccharomyces cerevisiae were selected to minimize the effects of long-term refrigeration on the physicochemical properties and microstructure of fermented doughs. Compared to the control group without mixed yeast strains and additives, the fermentation properties, textural properties, dynamic rheology, starch crystallinity, protein structure, water distribution, and microstructure were investigated by mixed yeast strains and additives for 14 days of long-term refrigeration. The results showed that using mixed yeast strains (Saccharomyces cerevisiae: Metschnikowia pulcherrima; Wickerhamomyces anomalous = 0.46:0.27:0.27), α-amylase, diacetyl tartaric acid ester of mono(di)glycerides and polydextrose can avoid the excessive fermentation of refrigerated dough. In addition, mixed yeast strains and additives could maintain the orderliness of the secondary structure of gluten proteins, stabilize the microstructure of starch and gluten proteins, and reduce the migration and loss of water in the dough. This study clarified that mixed yeast strains and additives are conducive to prolonging the long-term refrigeration of dough, and could better maintain the quality of dough during long-term refrigeration. These results provide a theoretical basis for further research on the large-scale production of refrigerated fermented dough.